2015
DOI: 10.1186/s13019-015-0271-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two different mechanical esophagogastric anastomosis in esophageal cancer patients: a meta-analysis

Abstract: ObjectiveIn this meta-analysis, we conducted a pooled analysis of clinical studies comparing Linear Stapled (LS) versus Circular Stapled (CS) esophagogastric anastomosis for esophageal cancer.MethodsAccording to the recommendations of the Cochrane Collaboration, we established a rigorous study protocol. We performed a systematic electronic search of the PubMed, Embase, Cochrane Library, Web of Science, and Chinese Biomedical databases as well as Chinese scientific journals to identify articles to include in ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 19 publications
1
41
1
5
Order By: Relevance
“…A recent meta‐analysis found lower leak rates with a linear stapled esophagogastric anastomosis compared to a completely hand‐sewn technique . A separate meta‐analysis by the same authors found no difference in leak rates between linear stapled and circular stapled esophagogastric anastomoses, but there were significant different stricture rates . A recent analysis using the Society of Thoracic Surgeons General Thoracic Database found an overall leak rate of 10.6% among 7595 esophagectomies, with rates of 12.3% and 9.3% for cervical and intrathoracic anastomosis, respectively .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta‐analysis found lower leak rates with a linear stapled esophagogastric anastomosis compared to a completely hand‐sewn technique . A separate meta‐analysis by the same authors found no difference in leak rates between linear stapled and circular stapled esophagogastric anastomoses, but there were significant different stricture rates . A recent analysis using the Society of Thoracic Surgeons General Thoracic Database found an overall leak rate of 10.6% among 7595 esophagectomies, with rates of 12.3% and 9.3% for cervical and intrathoracic anastomosis, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…Different esophagogastric anastomotic techniques have their own characteristics, and multiple reports have compared anastomotic complications among various techniques . A side‐to‐side anastomosis has been generally defined as a semi‐mechanical liner stapler procedure, and in several studies it has been shown to reduce the incidence of postoperative anastomotic strictures without increasing the rate of anastomotic fistulae . At present, there are relatively few studies using a mechanical anastomosis, especially as it is applied to cervical anastomoses during MIE procedures .…”
Section: Introductionmentioning
confidence: 99%
“…La diferencia con nuestros resultados puede deberse a la falta de homogeneidad en la técnica utilizada, pues se in-cluyeron pacientes con diferentes tipos de anastomosis con sutura mecánica 28 . En la presente serie, no se encontró una diferencia significativa en las complicaciones al usar sutura mecánica circular o lineal, en forma similar a lo informado por Zhou, et al, en su metaanálisis sobre fugas de las anastomosis; ellos informaron también un aumento de las estenosis, un aspecto que no fue evaluado en este estudio 29 . Al comparar la cirugía convencional con las técnicas mínimamente invasivas, los resultados coinciden con los de Findlay, et al, quienes no encontraron diferencias estadísticamente significativas en las tasas de fugas de la anastomosis (mínimamente invasiva, 17,9 %; híbrida, 11,6 %, y abierta, 12,6 %); y también, con los del metaanálisis de Yibulayin, et al, cuyos porcentajes de complicaciones fueron similares (mínimamen-te invasiva 41,5 % y abierta 48,2 %) 30,31 .…”
Section: Discussionunclassified
“…Currently, there is no evidence to indicate that the additional esophageal resection in the neck reduces tumor recurrence or improves survival . For late complications, such as anastomotic strictures, the location of the anastomosis per se does not seem to influence stricture rates, but rather the preferred anastomotic technique appears more significant (i.e., fewer for hand‐sewn and linear stapled versus circular stapled) …”
Section: Surgical Techniquesmentioning
confidence: 99%
“…133,136 For late complications, such as anastomotic strictures, the location of the anastomosis per se does not seem to influence stricture rates, but rather the preferred anastomotic technique appears more significant (i.e., fewer for hand-sewn and linear stapled versus circular stapled). 140 In general, studies comparing intrathoracic and cervical anastomosis after esophageal surgery have relatively small sample sizes and considerable variation with regard to surgical approach and technique. These limitations increase the need for further studies to more accurately determine possible differences between intrathoracic and cervical anastomoses.…”
Section: Cervical Versus Intrathoracic Anastomosismentioning
confidence: 99%